Regional input on the social dimension of Ezoneplus: Belgium, The Netherlands, France, Austria and Germany - Achim Kemmerling (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This Regional Input is a supplement to Ezoneplus Working Paper No. 13 on the Social Dimension of the Eastward Enlargement of the Eurozone. Within Ezoneplus the Social Dimension is a hybrid in the sense that it addresses both the reshaping of certain policies and the socio-political repercussions an Eastward enlargement of the euro-zone may have. Correspondingly, key questions to be answered can be grouped under two headings: Firstly, what kind of external shocks does EU enlargement, and more specifically, the enlargement of EMU produce on national and EU policies? The three policy areas here to be inspected are social security systems, labour market regulation, and EU structural and agricultural policy. Secondly, how do national societies and political systems respond to these new constraints? This implies both potential social conflicts enhanced by the enlargement process, as well as their implications for national policy-making. In order to combine both topics, we suggest an analysis using insights of modern political economy. In brief, this is to say that rational political actors act in response to Ezoneplus in a way predictable once the socioeconomic outcomes of the enlargement process have been analysed.
Keywords: 330; Regional Input; Belgium; The Netherlands; France; Austria; Germany